2006
DOI: 10.1533/ijcr.2005.0387
|View full text |Cite
|
Sign up to set email alerts
|

Feedback control of occupant motion during a crash

Abstract: Passive in-vehicle safety systems such as the air bag and the belt restrain the occupant during a crash. However, often their behavior is not optimal in terms of occupant injuries. This paper discusses an approach to design an ideal restraint system. The problem is formulated as a feedback tracking problem with the objective to force the controlled variables, i.e., the acceleration of the head and the chest of the occupant, to follow a priori defined reference signals by simultaneous manipulation of the belt a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Because of tube functionality, technological process must assure the circular section form in every interior point of the tube. Any geometrical deviation from the circular shape can generate lost pressure so the pre-tensioning system will have not the same effect [4]. This is why a test method should be created to evaluate the variation of the pressure in the tube.…”
Section: Functionality Of the Tube In Pre-tensioningmentioning
confidence: 99%
“…Because of tube functionality, technological process must assure the circular section form in every interior point of the tube. Any geometrical deviation from the circular shape can generate lost pressure so the pre-tensioning system will have not the same effect [4]. This is why a test method should be created to evaluate the variation of the pressure in the tube.…”
Section: Functionality Of the Tube In Pre-tensioningmentioning
confidence: 99%
“…Bio-medically, adaptive seat belt shows an increasing level of occupant protection during different impact scenarios [9]. The applied force on the occupant's chest has to be limited (between 3-8 KN) in order to avoid the risk of irreversible thoracic injuries.…”
Section: Introductionmentioning
confidence: 99%
“…As further developments, with the help of simulations, there are studies of advanced control schemes, such as control of seatbelt displacement at the retractor to achieve constant seat belt force (including belt retraction to build up belt force) [9] and feedback control of occupant motion [10]. It has been shown that these can provide improvements in occupant restraint.…”
Section: Introductionmentioning
confidence: 99%